Case report: FGF4L1 retrogene insertion is lacking in the tall dachshund phenotype - Sullivan, Stacey; Szeremeta, Katarzyna Julia; Kutzler, Michelle (Frontiers in Veterinary Science, 2025)
Two retrogene insertions, FGF4L1 (formerly 18-FGF4, colloquially CDPA) and FGF4L2 (formerly 12-FGF4, colloquially CDDY), have recently been discovered as determinants of short leg phenotype in dogs. This case study is comprised of a family of standard wirehaired dachshunds in which the dogs lacking the FGF4L1 gene exhibit a tall phenotype. The tall phenotype in the dachshunds of this report precludes the dog’s working function of den work. The data presented in this report provide information as to how FGF4L1 status could be used in making breeding decisions in dachshunds to maintain working ability without compromising animal health.